The Urban Wage Premium in Imperfect Labour Markets - Boris Hirsch; Elke J. Jahn; Michael Oberfichtner (Institute for the Study of Labor (IZA), 2016)
Using administrative data for West Germany, this paper investigates whether part of the urban wage premium stems from fierce competition in thick labour markets. We first establish that employers possess less wage-setting power in denser markets. Local differences in wage-setting power predict 1.1-1.6% higher wages from a 100 log points increase in population density. We further document that the observed urban wage premium from such an increase drops by 1.1-1.4pp once conditioning on local search frictions. Our results therefore suggest that a substantial part of the urban wage premium roots in differential imperfections across local labour markets.
Keywords: R23; J42; J31; 330; urban wage premium; imperfect labour markets; monopsony; search frictions